The effect of melatonin on cardio fibrosis in juvenile rats with pressure overload and deregulation of HDACs - Wu, Yao (Korean J Physiol Pharmacol, 2018)
The effect of melatonin on juveniles with cardio fibrosis is poorly understood. We investigated whether HDACs participate in the anti-fibrotic processes regulated by melatonin during hypertrophic remodeling. Abdominal aortic constriction (AAC) was employed in juvenile rats resulting in pressure overload-induced ventricular hypertrophy and melatonin was subsequently decreased via continuous light exposure for 5 weeks after surgery. AAC rats displayed an increased cross-sectional area of myocardial fibers and significantly elevated collagen deposition compared to sham-operated rats, as measured by HE and Masson Trichrome staining. Continuous light exposure following surgery exacerbated the increase in the cross-sectional area of myocardial fibers. The expression of HDAC1, HDAC2, HDAC3, HDAC4 and HDAC6 genes were all significantly enhanced in AAC rats with light exposure relative to the other rats. Moreover, the protein level of TNF-α was also upregulated in the AAC light exposure groups when compared with the sham. However, Smad4 protein expression was unchanged in the juveniles' hearts. In contrast, beginning 5 weeks after the operation, the AAC rats were treated with melatonin (10 mg/kg, intraperitoneal injection every evening) or vehicle 4 weeks, and sham rats were given vehicle. The changes in the histological measures of cardio fibrosis and the gene expressions of HDAC1, HDAC2, HDAC3, HDAC4 and HDAC6 were attenuated by melatonin administration. The results reveal that melatonin plays a role in the development of cardio fibrosis and the expression of HDAC1, HDAC2, HDAC3, HDAC4 and HDAC6 in cardiomyocytes.